Pengaruh financial self efficacy,financial knowledge dan locus of control terhadap pengelolaan keuangan pribadi mahasiswa fakultas ekonomi universitas pendidikan ganesha - Kadek Rindi; I Made Pradana Adiputra (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of financial self efficacy, financial knowledge and locus of control of the personal financial management. This study is quantitave study with 88 respondent of collage stundent in Economic Faculty Ganesha University of Education. The data obtained by distributing questionnaires using the google form service. The criteria for the selected samples were using the purposive sampling technique then calculated by the slovin formula . the data of this study are the from of respondents’answers as the primary data then processed using SPSS version 20. The results achieved the goals of this study in which the financial self efficacy, financial knowledge, and locus of control have positives and significant effect of personal financial management Keywords : financial self efficacy, financial knowledge, locus of control, personal financial management.